PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Darmayasa, I Gede; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Changes or modernization of the tax administration system is one of the government's efforts in improving taxpayer compliance. Changes made covering the areas of organizational structure, business processes and information technology and communications, human resource management, and implementation of good governance. The purpose of this study was to determine the influence of modernization of the tax administration system on taxpayer compliance. Tax Office (KPP) Pratama Badung Utara used for research by selecting individual taxpayer (WPOP) as the study sample. The sample used was 100 WPOP with cluster sampling technique. Techniques of data collection is done by using a questionnaire. This study tested using multiple linear regression analysis. Based on the results of the analysis can be concluded that the variables of the organizational structure, human resource management and good governance have a significant effect on tax compliance. Variable business process and information technology and communications have no effect on tax compliance in the Tax Office (KPP) Pratama Badung Utara.
Keywords: modernization of the tax administration system, compliance